Peningkatan Kreativitas Seni Anak melalui Kegiatan Kolase - Umairi, Mushab Al; Fatmawati, Fitri Ayu; Amalia, Dwi Rizky (Journal of Childhood Education, Development and Parenting, 2024)
This research is motivated by the importance of improving artistic abilities in early childhood appropriately and optimally, so as not to influence other aspects of development, because aspects of development in early childhood can influence each other. This research aims to describe or find out descriptions of artistic abilities in children aged 5-6 years through coloring activities. This research uses a literature study with a descriptive qualitative approach, using primary data sources consisting of journals and books that are appropriate to the researcher. This research focuses on artistic abilities in children aged 5-6 years which can develop optimally through coloring activities. The results of this research show that implementing coloring activities can optimize artistic abilities in children aged 5-6 years, such as coloring activities using 3-dimensional methods through project learning, graffiti techniques, and many more, so that they can be in accordance with the theme and material. what you want to convey to your child.